2016
DOI: 10.1039/c5sc03059e
|View full text |Cite
|
Sign up to set email alerts
|

A genomics-led approach to deciphering the mechanism of thiotetronate antibiotic biosynthesis

Abstract: A novel mechanism is proposed for ring formation in the biosynthetic pathway to thiotetronate antibiotics thiolactomycin and Tü 3010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…[23] Leadlay and co-workers previously reported the gene inactivation of stuD1 and tlmD1 , two homologs of the CYP450-encoding gene tlmF , in two separate TLM-producing strains, that led to the elimination of TLM production without detecting any additional products. [18] Thus, our findings not only support the essential role of the CYP450 TlmF in the formation of the 5-membered thiolactone ring, but the identification of compound 5 further implicates that the insertion of sulfur into TLM is independent of TlmF.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…[23] Leadlay and co-workers previously reported the gene inactivation of stuD1 and tlmD1 , two homologs of the CYP450-encoding gene tlmF , in two separate TLM-producing strains, that led to the elimination of TLM production without detecting any additional products. [18] Thus, our findings not only support the essential role of the CYP450 TlmF in the formation of the 5-membered thiolactone ring, but the identification of compound 5 further implicates that the insertion of sulfur into TLM is independent of TlmF.…”
supporting
confidence: 58%
“…Simultaneously, others identified similar BGCs in four different strains. [18] These findings revealed that 1 and its analogues are constructed via an unconventional PKS-NRPS hybrid assembly line, indicating an unusual biosynthetic logic at play. Here we report the exploration of the biosynthesis of the tlm BGC from S. pacifica CNS-863 through genetic and analytical strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…188,189 This ring, found at the C-terminus of the molecule, contains a sulfur atom that originates from the side chain of cysteine that is selected and activated by the nal module of the PKS/NRPS. Following this, the exact mechanism by which the sulfur is inserted into the molecule is unclear, although the role of the P450 is believed to centre on the epoxidation of the C4-C5 double bond (Fig.…”
Section: 188mentioning
confidence: 99%
“…However, an increasing number of PKS systems are now known in which the main product apparently requires iterative use of a module to accomplish two or even three successive rounds of chain extension. First noted in the stigmatellin PKS from Stigmatella aurantiaca [20], further examples have been uncovered in the PKSs for aureothin [2122], borrelidin [2324], lankacidin [2526], neoaureothin [27], etnangien [28], crocacin [29], ebelactone [30] and thiolactomycin [3132]. Given the close mechanistic analogy between fatty acid synthases and an iterative PKS module, it is instructive that a normally colinear extension module of the pikromycin PKS, when studied as a stand-alone protein in vitro, catalyses two rounds of polyketide chain extension [19].…”
Section: Introductionmentioning
confidence: 99%